Trade, food, diet, and health : perspectives and policy options - Hawkes, Corinna (Blackwell Publication, 2010)
Examines how the global food trade regime - the trade of food across national borders, international and regional trade agreements, the process of trade and investment liberalization and the growth of transnational food corporations - affects what people eat and, by implication, their health.